2013
DOI: 10.1140/epje/i2013-13014-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of complex solvents on the structure and dynamics of protein solutions: The case of Lysozyme in trehalose/water mixtures

Abstract: Abstract. We present a Molecular Dynamics simulation study of the effect of trehalose concentration on the structure and dynamics of individual proteins immersed in trehalose/water mixtures. Hen egg-white Lysozyme is used in this study and trehalose concentrations of 0%, 10%, 20%, 30% and 100% by weight are explored. Surprisingly, we have found that changes in trehalose concentration do not change the global structural characteristics of the protein as measured by standard quantities like the mean square devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…This possibly leads to its superior cryo-and lyoprotective properties [130]. MD simulations have been also performed in ternary LSZsugar-water systems at various sugar concentration [131][132][133][134]. More recently, a simulation of a solid state system composed by several LSZ proteins embedded in a low water glassy trehalose matrix has shown the presence of a more tight molecular packing of the proteins, which impairs the formation of large voids present in the dry LSZ glass without sugar [46].…”
Section: Atomistic Levelmentioning
confidence: 99%
“…This possibly leads to its superior cryo-and lyoprotective properties [130]. MD simulations have been also performed in ternary LSZsugar-water systems at various sugar concentration [131][132][133][134]. More recently, a simulation of a solid state system composed by several LSZ proteins embedded in a low water glassy trehalose matrix has shown the presence of a more tight molecular packing of the proteins, which impairs the formation of large voids present in the dry LSZ glass without sugar [46].…”
Section: Atomistic Levelmentioning
confidence: 99%
“…TDFSS ,, of protein solutions even suggested the dramatic slowdown of water mobility by several orders of magnitude. To summarize, although the results of both experiments , , and computer simulations suggested that water dynamics are retarded by the protein molecules, quantitative descriptions of the slowdown in hydration water dynamics remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Also, previous simulations were carried out for shorter timescales, at lower temperature and for concentrated solutions and do not cover the study of dynamics at several temperatures. 19,[31][32][33][34] Some of them are intended to explain the cryopreservation and dehydration of protein. In this study, we have focused on the effect of trehalose against thermal denaturation and hence the study was carried out in the high temperature regime and in dilute aqueous solution.…”
Section: Introductionmentioning
confidence: 99%